CULTURAL BASED TOURISM DEVELOPMENT IN PASIR PUTIH VILLAGE TUKAK SADAI DISTRICT, BANGKA SELATAN DISTRICT THROUGH AGIK BARIK FESTIVAL - Darwance Darwance; Dwi Haryadi; Izma Fahria; Agung Samudra; Desy Ramadhanty; Erika Erika (Berumpun: International Journal of Social, Politics, and Humanities, 2019)
Education, culture and tourism are three things that cannot be separated and interconnected. Culture will develop if education develops too. By education, culture will increase the development of tourism in Indonesia. In order to improve the quality and progress of education, culture and tourism, Social Service Lecture (KKN) XIV Bangka Belitung University (UBB) 2019 Pasirputih - Sadai Desa Pasirputih region, develop tourist destinations through the program "Festival Paserpute Agik Barik" (cultural festival Pasirputih in the past), this activity aims to explore the history and culture of the original tempo of the past (past) in the Pasirputih Village, be it cultural heritage, customs, arts, culinary, traditional games, crafts, and also practice and historical habits the life of the local community in the past, which will be re-demonstrated as the superiority of the Village later and can also be introduced to the wider community as a destination for natural and cultural tourism, which will become its own characteristics and not found elsewhere.